Prescrição de medicamentos por enfermeiros na atenção básica no Brasil: Questões e perspectivas sobre a sua legitimidade - Nascimento, Wezila Gonçalves do (2018)
Introduction: Among the actions developed by the nurse in Primary Care, emphasis has been placed on the assignment of prescribers under the Professional Nursing Practice Act since 1986 in the public health programs. In the Family Health Strategy, this assignment has been increasingly used, integrating the care provided by this professional. However, on the one hand, it has been facing professional battles when exercising prescriptive action, and on t he other hand, it is unknown how users perceive this issue. Objectives: This study aims to evaluate the prescription of drugs by nurses in Primary Care in Brazil, based on the institution established by the representative bodies of the category and legitimized by the users. Material and methods: A Case Study was conducted using document analysis techniques and interviews. For the documentary study, documents of institutional authorship - Federal Nursing Council (COFEN), its regional representations in the respective states of Brazil (COREN) and Brazilian Nursing Association (ABEN) were used and with open access. The interviews were performed with 30 users of the health units who were waiting to undergo the nursing consultation. Results: the documentary study revealed that the convincing arguments of the representative entities regarding the prescription of medications and request and examinations by nurses are based on three categories: Autonomy and competencies for the prescription of medications and / or request for exams; Corporate policies that undermine the full exercise of nursing and the transformation of health and nursing care in Primary Health Care. The results of the field research were organized in two dimensions: general and specific. In the general dimension the following categories emerged: Knowledge about the health- disease process; Understanding about ESF and Perception about the ESF Nurse. In the specific dimension emerged: Knowledge about the health-disease process and Drug Prescription by nurses from the perspective of the users. The users eventually revealed the lack of understanding regarding their own health, lack of knowledge about the services offered and the role of the nurses in the FHT, emphasizing nurses as professionals qualified to manage the services and to perform complementary duties tasks the prescription of medicines is perceived as a substitutive activity, not a legal profession. Conclusion: the prescriptive practice of nurses integrates health care and has been defended by the representative entities of the category, however they are not recognized as an attribution of the nurse by the users of the service, being emptied by perceptions that make the profession of lower value, being so it is necessary that the nursing profession be disseminated and emphasized within its power, in the capacity to produce care based on scientific evidence.